Análise da flexibilidade e da postura em jovens atletas praticantes de futebol - Mondoni, Gustavo Henrique de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
there is evidence that sport can trigger the onset of postural patterns specific to each modality, regardless of the geopolitical aspects, social, cultural habits of everyday life and ethnicity. Since changes in flexibility are cited as possible precursors of decreased range of motion, thereby harming the mechanics of the lower limbs and gait. Objetcive: The objective of this study was to analyze changes in posture and flexibility in young soccer players. Methods: were assessed 51 youngsters, aged between 14 and 18 years, soccer players registered in the Municipal Presidente Prudente SP and categories of the base of Gremio of Presidente Prudente. Data were collected from the assessment by the postural software assessment, and flexibility tests the Bench, to jail and later by tests of muscle length to jail earlier proposed by Kendall et al , was also collected anthropometric data were later confronted with the results statistically. The results were organized into spreadsheets for computing, which later could be performed the statistical analysis. Values are expressed by means of central tendency and variability as well as medians and 95% confidence intervals. The comparison for each profile height and BMI was made by means of analysis of variance complemented by Tukey test. Were considered the statistical differences when P <0.05. Results: In the sample studied 64% of the subjects classified as normal posture, the same happened with 70.59% of the athletes for flexibility in relation to the center of gravity of the sample had 100% anterior displacement of the trunk and 86.28% with a deviation of center of gravity to the left, showing a tendency to some postural deviations for the group assessed. Conclusion: from the results we can conclude that there was significant relationship between the postural angle of the right leg and left angle of the pelvis with BMI and also ankle angle... (Complete abstract click electronic access below)

há evidências de que o esporte pode desencadear o aparecimento de padrões posturais específicos de cada modalidade, independentemente dos aspectos geopolíticos, sociais, culturais, hábitos do cotidiano e etnia. Já alterações de flexibilidade são citadas como possíveis precursoras da diminuição de amplitude de movimento (ADM), prejudicando dessa forma, a mecânica dos membros inferiores e da marcha. Objetivo: o objetivo do presente estudo foi analisar as alterações posturais e de flexibilidade em jovens praticantes de futebol. Métodos: foram avaliados 51 jovens, com idade entre 14 e 18 anos, praticantes de futebol registrados na Secretaria Municipal de Presidente Prudente SP (SEMEPP) e das categorias de base do Grêmio de Presidente Prudente. Os dados obtidos foram coletados a partir da avaliação postural por meio do software de avaliação postural (SAPO), e dos testes de flexibilidade do banco de Wells, para a cadeia posterior e pelos testes de comprimento muscular para a cadeia anterior propostos por Kendall et al, coletou-se também os dados antropométricos que posteriormente foram confrontados estatisticamente com os resultados encontrados. Os resultados obtidos foram organizados em planilhas computacionais para que, posteriormente, pudesse ser realizada a análise estatística. Os valores foram expressos por meio de tendência central e variabilidade além de medianas e intervalos de confiança 95%. A comparação para cada perfil de estatura ou IMC deu-se por meio de Analise de Variância complementado pelo teste de Tukey. Consideraram-se as diferenças estatísticas quando P<0,05. Resultados: Na amostra avaliada 64% dos indivíduos apresentaram postura classificada como normal, o mesmo ocorreu com 70,59% dos atletas quanto à flexibilidade, em relação ao centro de gravidade 100% da amostra apresentou deslocamento anterior do tronco e 86,28% com desvio... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fisioterapia